EARLY ACTIVE MOBILIZATION VS IMMOBILIZATION FOLLOWING MODIFIED KESSLER REPAIR OF EXTRINSIC EXTENSOR TENDONS IN ZONE V TO VII - Rabbani, Muhammad Jibran; Amin, Muhammad; Khalid, Kamran; Khan, Husnain; Shahzad, Imran; Rabbani, Ammara; Nasrullah, Muhammad; Tarar, Moazzam Nazeer; Rabbani, Sarah (Journal of Ayub Medical College Abbottabad, 2019)
Background: The long-disputed issue of rehabilitation of extensor tendon repairs in zones V-VII has been treated with either complete immobilization or mobilization within the constraints of splint. In recent times, most authors have preferred some mobilization. Many studies have shown good results with early mobilization techniques; however, these studies have limitations. Most of these are retrospective observations. Some prospective studies are without proper controls. This study was conductive to compare the functional outcome of early active mobilization versus immobilization following repair of extensor tendons in zone V-VII. Methods: Functional outcome was determined by total active motion, pain and complications during rehabilitation. Total active motion (TAM) was graded by scores of the American Society for Surgery of Hand as TAM=total active flexion (MCP+PIP+DIP)-total extension deficit (MCP+PIP+DIP). A randomized control trial was conducted including 50 subjects of with extensor tendon injury exclusively in zone V-VII. Patients were divided randomly in two groups. All extensor tendon repairs (zone V to VII) were performed with modified Kessler’s method. The pain and TAM was assessed during all visits in both groups except TAM in group B that was assessed after four weeks. Results: We found that outcome of 12% cases in Group A as excellent and no patient fell in category of fair results. While, in comparison, there was no case of excellent result in Group B. 4% cases showed fair results that were treated with immobilization. The pain score at the end of treatment, i.e., at 12 weeks were same in both the groups but, generally the score remained higher in group of EAM. There was significant difference in adhesion formation that was more in patients of immobilization group. The overall suture dehiscence was insignificant and was only 8% in each group. Conclusion: EAM has better outcome in terms of pain and range of motion. Keywords: Extensor tendon injury; Zone V; zone VI; zone VII; Early active mobilization